2019
DOI: 10.1177/2050312119840195
|View full text |Cite
|
Sign up to set email alerts
|

Rescue treatment in patients with poorly responsive Guillain–Barre syndrome

Abstract: Objectives:To evaluate the effectiveness of rescue treatment (intravenous immunoglobulin or plasma exchange) in patients with Guillain–Barre syndrome who did not respond or deteriorated after the initial management with intravenous immunoglobulin.Methods:We performed a retrospective review of the medical records of patients who responded poorly or did not respond to intravenous immunoglobulin treatment. The disability parameters of those who received second-line treatment with intravenous immunoglobulin or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
(24 reference statements)
0
8
0
2
Order By: Relevance
“…2,4,43,46 One point that needs to be clarified is when the first line of treatment is not successful what should be the correct approach, even because there is a study stating that the patients submitted to a second course of therapy had a lengthier hospital stay and slower motor recovery (nevertheless, there could be some improvement at the end of the first month of treatment, although at 3 and 6 months the differences were not significant, with a large amount of loss to follow-up). 27 There are not many studies, particularly in children, where both PLEX and IgIV are used simultaneously. In one of the few early articles 47 there were no significant differences between using each technique alone or in combination.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,43,46 One point that needs to be clarified is when the first line of treatment is not successful what should be the correct approach, even because there is a study stating that the patients submitted to a second course of therapy had a lengthier hospital stay and slower motor recovery (nevertheless, there could be some improvement at the end of the first month of treatment, although at 3 and 6 months the differences were not significant, with a large amount of loss to follow-up). 27 There are not many studies, particularly in children, where both PLEX and IgIV are used simultaneously. In one of the few early articles 47 there were no significant differences between using each technique alone or in combination.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,43,46 One point that needs to be clarified is when the first line of treatment is not successful what should be the correct approach, even because there is a study stating that the patients submitted to a second course of therapy had a lengthier hospital stay and slower motor recovery (nevertheless, there could be some improvement at the end of the first month of treatment, although at 3 and 6 months the differences were not significant, with a large amount of loss to follow-up). 27 There are not many studies, particularly in children, where both PLEX and IgIV are used simultaneously. In one of the few early articles 47 there were no significant differences between using each technique alone or in combination.…”
Section: Discussionmentioning
confidence: 99%
“…So, a second line of treatment is still not well established, if the first course of treatment proves to be unsuccessful. 27…”
Section: Comparison Between Plex and Igivmentioning
confidence: 99%
“…Another study done by Godoy and Rabinstein 27 recommended a second cycle of IVIG for treating severe forms of GBS. A third study by Alboudi et al 28 concluded that a second course of rescue treatment using either IVIG or PLEX might be beneficial in carefully selected patients. Based on our experience and during discussions with neurologists in other centers, it is a common practice to give additional doses of IVIG for refractory cases or possible early chronic inflammatory demyelinating polyneuropathy.…”
Section: Discussionmentioning
confidence: 99%